Patent ductus arteriosus stenting versus modified Blalock–Taussig shunt for palliation of duct‐dependent pulmonary blood flow lesions. Issue 9 (21st June 2022) - Helal, Abdelmonem M.; Elmahrouk, Ahmed F.; Bekheet, Samia; Barnawi, Hani I.; Jamjoom, Ahmed A.; Galal, Mohammed O.; Abou Zahr, Riad
Abstract: Background: Patent ductus arteriosus (PDA) stenting is an alternative to modified Blalock–Taussig shunt (MBTS) as first‐stage palliation of duct‐dependent lesions. The superiority of one approach over the other is still controversial. Our objective was to compare PDA  stent versusMBTS for palliation in regard to safety, efficacy, and efficiency. Methods: From 2010 to 2021, 134 patients had first‐stage palliation with either PDA stent ( n  = 83) or MBTS ( n  = 51). Twenty‐seven patients failed the primary treatment and were converted to the other group. The study endpoints were hospital outcomes, interstage reintervention, and concomitant procedures at the second‐stage palliation. Results: Patients with PDA stent were significantly younger. The prevalence of antegrade pulmonary blood flow (PBF) was higher in patients who had MBTS and graft thrombosis was higher in the PDA stent. Hospital stay was significantly longer in patients who had MBTS. Predictors of prolonged mechanical ventilation were low‐weight, MBTS, and conversion. Intensive care unit stay significantly increased with conversion, low‐weight, and antegrade PBF. The interstage intervention was required more frequently in PDA‐stent group. Predictors of reintervention were conversion and pulmonary atresia with the intact interventricular septum. Pulmonary artery plasty was required more frequently during the second‐stage palliation in PDA‐stent group. Conclusion: PDA stent is an alternative to MBTS for first‐stage palliation. It is associated with shorter hospital stays and avoidance of surgery at the expense of a high rate of stent thrombosis and interstage reintervention. Conversion increased the risk of the procedure. More studies are needed to determine factors that affect PDA‐stent outcomes and patient selection criteria.